2008
DOI: 10.1021/jf800974z
|View full text |Cite
|
Sign up to set email alerts
|

Salicylic Acid sans Aspirin in Animals and Man: Persistence in Fasting and Biosynthesis from Benzoic Acid

Abstract: Salicylic acid (SA), which is central to defense mechanisms in plants and the principal metabolite of aspirin, occurs naturally in man with higher levels of SA and its urinary metabolite salicyluric acid (SU) in vegetarians overlapping with levels in patients on low-dose aspirin regimens. SA is widely distributed in animal blood. Fasting for major colorectal surgery did not cause disappearance of SA from plasma, even in patients following total proctocolectomy. A 13C6 benzoic acid load ingested by six voluntee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 27 publications
1
52
0
Order By: Relevance
“…Some permeant acids also cross the membrane in the unprotonated form and decrease the proton motive force (PMF); an example is benzoic acid (benzoate), a food preservative found in soft drinks and acidic foods (12). The related molecule salicylic acid (salicylate) is a plant defense regulator (13,14) as well as the primary active metabolite of acetylsalicylate (aspirin) (15)(16)(17). Salicylates enter the human diet from fruits and vegetables, leading to circulating plasma levels as high as 0.1 to 0.2 M (18).…”
mentioning
confidence: 99%
“…Some permeant acids also cross the membrane in the unprotonated form and decrease the proton motive force (PMF); an example is benzoic acid (benzoate), a food preservative found in soft drinks and acidic foods (12). The related molecule salicylic acid (salicylate) is a plant defense regulator (13,14) as well as the primary active metabolite of acetylsalicylate (aspirin) (15)(16)(17). Salicylates enter the human diet from fruits and vegetables, leading to circulating plasma levels as high as 0.1 to 0.2 M (18).…”
mentioning
confidence: 99%
“…To facilitate interpretation, we have incorporated the concentrations utilised in the relevant publications. We should also point out that whilst vegetables and fruits have been considered to be a www.intechopen.com natural source of salicylate, where it functions as a plant signalling molecule (Paterson & Lawrence, 2001;Schenk et al, 2000, and refs therein), it has been reported that SA may be an endogenous compound, with SA found in the blood of carnivorous animals, for example in the burrowing owl (Paterson et al, 1998;Paterson et al 2008). Fig.…”
Section: Mechanistic Aspects Of Nsaid Cytotoxicitymentioning
confidence: 98%
“…ii) Complete separation of the analytes is essential, because ASP undergoes source fragmentation in the mass spectrometer and forms SAL. iii) In addition, highly different calibration ranges are required for ASP and SAL because of the endogenous SAL levels in blank human plasma [28,29]. iv) In the case of partial separation of the analytes, the much higher SAL levels can lead to ion suppression in the source of the mass spectrometer.…”
Section: Optimizing the Analytical Systemmentioning
confidence: 99%